2006
DOI: 10.1172/jci27602
|View full text |Cite
|
Sign up to set email alerts
|

HDL from CETP-deficient subjects shows enhanced ability to promote cholesterol efflux from macrophages in an apoE- and ABCG1-dependent pathway

Abstract: Genetic deficiency or inhibition of cholesteryl ester transfer protein (CETP) leads to a marked increase in plasma levels of large HDL-2 particles. However, there is concern that such particles may be dysfunctional in terms of their ability to promote cholesterol efflux from macrophages. Recently, the ATP-binding cassette transporter ABCG1, a macrophage liver X receptor (LXR) target, has been shown to stimulate cholesterol efflux to HDL. We have assessed the ability of HDL from subjects with homozygous deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
196
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(214 citation statements)
references
References 47 publications
(42 reference statements)
16
196
2
Order By: Relevance
“…This is consistent with several reports that smaller particles are more active in cholesterol efflux [40,41], and our recent finding of a correlation between the ability of plasma to support cholesterol efflux and CETP concentration [12]. It is, however, inconsistent with findings that functionality of HDL particles formed as a result of inhibition of CETP was not impaired [42,43]. The only chemical modification of HDL known to increase its capacity to support cholesterol efflux is oxidative tyrosilation [44]; this was not tested in this study.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with several reports that smaller particles are more active in cholesterol efflux [40,41], and our recent finding of a correlation between the ability of plasma to support cholesterol efflux and CETP concentration [12]. It is, however, inconsistent with findings that functionality of HDL particles formed as a result of inhibition of CETP was not impaired [42,43]. The only chemical modification of HDL known to increase its capacity to support cholesterol efflux is oxidative tyrosilation [44]; this was not tested in this study.…”
Section: Discussionsupporting
confidence: 88%
“…LCAT activity may induce net cholesterol efflux via a non-specific cholesterol exchange mechanism (33). Very recently, it has been demonstrated that the presence of LCAT and apo E on a-HDL particles is important for cholesterol efflux out of macrophages (34). In our study, cholesterol efflux from fibroblasts was independently related both to plasma EST and to apo E.…”
Section: Discussionsupporting
confidence: 56%
“…therein). In plasma, apoE facilitates CE core expansion in HDL and thereby plays an important role in HDL metabolism, particularly in case of cholesterol ester transfer protein deficiency (33,34). Thus, apoE-containing HDL, which may be generated during lipolysis of TG-rich proteins, are important players in lipoprotein metabolism.…”
Section: Discussionmentioning
confidence: 99%